Exercise training attenuates dexamethasone-induced hypertension by improving autonomic balance to the heart, sympathetic vascular modulation and skeletal musclemicrocirculation - Herrera, Naiara A. [UNESP]; Jesus, Isley [UNESP]; Shinohara, André L.; Dionísio, Thiago J.; Santos, Carlos F.; Amaral, Sandra L. [UNESP] (Wolters Kluwer, 2016)
Objective: Although aerobic exercise training has been recommended as nonpharmacological treatment of high blood pressure, the mechanisms of training-induced blood pressure lowering effects in dexamethasone (DEX)-induced hypertension remain unclear. Therefore, the aim of this study was to investigate the preventive role of exercise training in counteracting DEX-induced hypertension. Methods: Rats were submitted to aerobic exercise training for 8 weeks or kept sedentary and then treated with DEX (50mg/kg/day, s.c.) or saline injections for 14 days. Thereafter, all rats underwent carotid artery catheterization, and cardiovascular autonomic modulation was evaluated by spectral analysis. In addition, soleus muscle was collected for morphometric and protein level analysis. Results: DEX treatment increased arterial pressure concomitantly with an increase in low-frequency spectral power of systolic arterial pressure and low frequency in pulse interval (94.11 and 58.58%, respectively), and a decrease in high-frequency spectral power of pulse interval (12.05%). Capillary density (25.87%), capillary-To-fibers ratio (21.22%), vascular endothelial growth factor level (15.10%), B-cell lymphoma 2 (Bcl-2) level (16.40%) and Bcl-2/Bcl-2 associated X protein ratio (27.14%) were all decreased after DEX treatment. Exercise training attenuated DEX-induced increase in arterial pressure accompanied by an attenuation of low-frequency spectral power of systolic arterial pressure, low frequency in pulse interval increases and high-frequency spectral power of pulse interval decrease. Training also prevented the decrease in capillary density (R44.43%), capillary-To-fibers ratio (±36.97%), vascular endothelial growth factor (±16.46%), Bcl-2 (±15.21%) protein level and Bcl-2/Bcl- 2-Associated X protein ratio (±30.93%). Conclusion: These results demonstrate that exercise training improves cardiovascular autonomic balance to the heart associated with an improvement in sympathetic modulation of vascular tone and microcirculatory function in the skeletal muscle of DEX-induced.
Keywords: Apoptosis; Arterial pressure; Glucocorticoids; Physical training; Spectral analysis